2016
DOI: 10.21614/chirurgia.111.5.393
|View full text |Cite
|
Sign up to set email alerts
|

Patients After Splenectomy: Old Risks and New Perspectives

Abstract: Rezumat Pacienåii post-splenectomie: complicaåii cunoscute aei perspective noiComplicaåiile care survin în urma splenectomiei pot fi împãråite în infecåioase aei non-infecåioase. Legãtura dintre splenectomie aei aceste riscuri este doar paråial înåeleasã. Rãspunsul imun al gazdei împotriva infecåiei este profund modificat post-splenectomie, iar aceaeti indivizi sunt mai susceptibili sã dezvolte sepsis aei infecåia are o evoluåie fulminantã. Splenectomia este de asemenea un potenåial factor de risc pentru numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 79 publications
(86 reference statements)
2
23
0
6
Order By: Relevance
“…Purportedly, a body of miRNAs have been proved to regulate genes correlated with HDL metabolism, especially miR- 33a/b [ 60 ], which may contribute to ABCA1 expression at the same time, while many others, such as miR-148a, miR-128-1, or miR-30c, are involved in controlling circulating LDL concentrations as well as hepatic LDLR expressions [ 61 ]. Shifts in miRNAs expression after splenectomy may possibly take part in the development of AS [ 62 ]. But the accurate mechanism remains still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Purportedly, a body of miRNAs have been proved to regulate genes correlated with HDL metabolism, especially miR- 33a/b [ 60 ], which may contribute to ABCA1 expression at the same time, while many others, such as miR-148a, miR-128-1, or miR-30c, are involved in controlling circulating LDL concentrations as well as hepatic LDLR expressions [ 61 ]. Shifts in miRNAs expression after splenectomy may possibly take part in the development of AS [ 62 ]. But the accurate mechanism remains still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Prophylactic administration of pneumococcal vaccine or polymicrobial vaccine would reduce the infection and mortality rates. Some studies indicated that most of the infections occur in the first 2 years following splenectomy [23]. Blood cultures from peripheral venous blood or abscess cultures content allow the isolation of aerobic or anaerobic germs in automated BACTEC systems.…”
Section: Resultsmentioning
confidence: 99%
“…Infecção fulminante pós-esplenectomia: o mais importante, tanto pela frequência quanto pela mortalidade, é a infecção fulminante pós-esplenectomia (IFPE), cujo risco de um paciente esplenectomizado desenvolver é, pelo menos, 35 vezes maior que em indivíduos não esplenectomizados (SABATINO; CARSETTI; CORAZZA, 2011; MARQUES; PETROIANU, 2003;DRAGOMIR et al, 2016).…”
Section: O Paciente Pós-esplenectomiaunclassified
“…Outros riscos: Pacientes esplenectomizados também têm riscos aumentados para eventos tromboembólicos e para qualquer grau de disfunção da imunidade humoral, ocorrendo, no entanto, em menor frequência, com menor mortalidade e com risco para tais eventos muito menor que para a IFPE (SABATINO; CARSETTI; CORAZZA, 2011; DRAGOMIR et al, 2016).…”
Section: O Paciente Pós-esplenectomiaunclassified